valuation of the Hospital Service Indicator Reporting Application at Hospital X - Arifin, Ismail; Heltiani, Nofri; Khairunnisyah (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning Medical Records states that every health service must conduct electronic medical record activities, one of which is reporting hospital service indicators. Hospital X's reporting application has not been fully implemented and utilized. This is because it only provides menus for BOR and AvLOS indicators, resulting in calculations using the application differing from manual calculations. The purpose of this study was to evaluate the Hospital Service Indicator Reporting Application at Hospital X in 2024. This study was qualitative with a phenomenological approach. The subjects were medical records and IT staff, as well as the reporting application participants. The data used in this study were primary data, using interview guidelines and observation sheets. The data were then processed and analyzed univariately. The results of this study show that there is a difference in the number of beds between the BOR and AvLOS indicator menus in the reporting application and the Decree of the Director of Hospital X, resulting in differences in the calculation results of Hospital service indicators based on the 2006 Indonesian Ministry of Health which can result in errors in decision making, while the TOI and BTO indicator menus are not yet available so it is necessary to develop a Hospital reporting system design.